Aberrant Expression of PHLPP1 Correlates with Poor Prognosis in Patients with Gastric Cancer - Ya-Chao Hou; Han Liang; Jing-Yu Deng (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: The aim of this study was to investigate the expression of PHLPP1 in gastric cancer (GC), its potential influence on the prognosis of GC patients. Methods: In the present study, we examined the immunohistochemical expression of PHLPP1 on tissue microarrays (TMAs) containing 135 gastric adenocarcinoma tissues and 135 matched adjacent non-tumor tissues. Survival analysis according to PHLPP1 expression was calculated. Results: The majority of the adjacent non-tumor tissues showed positive-expression levels of PHLPP1 was 87.4% (118/135). In contrast, the positive rate of PHLPP1 in primary gastric cancer tissues was only 55.6% (75/135), significantly lower than that in adjacent non-tumor tissues (P<0.001). The Kaplan-Meier analysis showed that the overall survival (OS) rates of patients with negative PHLPP1 was significantly lower than that of patients with positive PHLPP1 (P=0.008). Multivariate survival analysis results showed that PHLPP1 was an independent predictor of the survival of patients with GC. Conclusion: This study indicates that aberrant expression of PHLPP1 was observed in GC and loss of PHLPP1 might identify patients with poor prognostic outcomes.